NUTRITIONAL QUALITY OF SIXTEEN TERRESTRIAL WEEDS FOR THE FORMULATION OF COST-EFFECTIVE ANIMAL FEED - Khan; R.; M. A. Khan; S. Sultan; K. B. Marwat; I. Khan; G. Hassan; H. U. Shah (Journal of Animal and Plant Sciences, 2013)
Nutritional composition of sixteen weeds was investigated to determine their nutritional potential for livestock consumption in Pakistan. Analysis of dry matter, ash, crude fiber, acid detergent fiber, nutrient detergent fiber and crude protein were conducted in Dicanthium annulatum, Cynodon dactylon, Avena fatua, Convolvulus arvensis, Sorghum halepense and Amananthus Viridis. Most of the species were rich in calcium, zinc, copper, iron, sodium and magnesiumwith the highest values recorded in Oxalis debilis, Rumex crispus, Medicago polymorpha, P. oleracea and A. viridis. Overall results indicated that broadleaf weeds possess higher mineral contents than grassy weeds. Results indicate that weeds can be used as a source of nutrients in livestock feeding, which will also help in promoting growth of the major corps. The grasses (A. fatua, D. annulatum and C. rotundus) could be important sources of fiber while broad leaf weeds (C. arvensis, A. viridis, and R. crispus) could be good sources of protein and minerals.
Keywords: weeds; feed; livestock; terrestrial; nutrients composition; protein; minerals; energy